Correction to: Routine diagnostics for neural antibodies, clinical correlates, treatment and functional outcome (Journal of Neurology, (2020), 10.1007/s00415-020-09814-3) - Bien, Christian G.; Bien, Corinna I.; Dogan Onugoren, Müjgan; De Simoni, Desiree; Eigler, Verena; Haensch, Carl Albrecht; Holtkamp, Martin; Ismail, Fatme S.; Kurthen, Martin; Melzer, Nico; Mayer, Kristina; von Podewils, Felix; et al. (Journal of Neurology, 2020)
The original version of this article unfortunately contained a mistake.
CRIS-Team Scopus Importer:2020-05-22